Ex Libris A. Brosza / [Z. Waśniewski]. - Waśniewski, Zygmunt (1921-1976) ([wydawca nieznany], 1966)
Na tle mozaiki stylizowana architektura i rycerz na koniu, napis u góry: Ex Libris, u dołu A. Brosza.